The Relationships Between Students' Attitudes Towards Information Technology, Computer Self-efficacy, Self-esteem And Their Academic Achievements In Koya University - Abdullah, Zhwan Dalshad (2015)
The purpose of the study was to investigate factors underlying the attitude towards IT and computer self-efficacy among students, and the relationships between students' attitudes towards information technology, the use of PowerPoint by lecturers in class, computer self-efficacy, and self-esteem with their academic achievements. The study approach was carried out via a quantitative method with a survey design. The sample size was selected from the second and fourth year students, consisted of 800 respondents who were randomly selected using proportional stratified random sampling from the Koya University. The survey consists of two sections. Section one contains the respondents' demographic information. Section two discusses the attitude towards IT, attitude towards the use of PowerPoint, computer self-efficacy, and self-esteem. The response rate was 85.1 %. The Principal Component Analysis (PCA), Pearson's correlation, and t-tests were run to answer the research questions. Principal Component Analysis used for the self-developed questionnaire produced three factor solutions of attitude towards IT, and two factor solutions of computer self-efficacy. The t-test results revealed a statistically significant difference between Arts and Science students in terms of their attitude towards IT and computer self-efficacy in favor of Science students. Furthermore, self-esteem is in favor of Arts students, with the exception of attitude towards PowerPoint, where no statistically significant difference was found.